Chemical and Isotopic Evaluation of a Microsampling Method using Laser Ablation and Membrane Filter. Issue 2 (24th April 2022) - Masuda, Yuki; Yokoyama, Tetsuya; Okabayashi, Satoki; Ishikawa, Akira; Iwamori, Hikaru
Abstract : Microscale isotopic measurements in geological materials are becoming of significant importance in geochemistry. This study evaluated the potential of a new microsampling method called laser ablation coupled with filter (LAF) for precise isotopic measurements of small‐sized geological materials, compared with conventional micromilling techniques. We optimised the system to maximise the sample collection rate and minimise the extent of the contamination. Isotope ratios ( 87 Sr/ 86 Sr, 142 Nd/ 144 Nd, 143 Nd/ 144 Nd, 206 Pb/ 204 Pb, 207 Pb/ 204 Pb and 208 Pb/ 204 Pb) of the glass reference material NIST SRM 610 collected using LAF were measured by thermal ionisation mass spectrometry, and no isotopic fractionation or blank effect was observed. This indicates that LAF can be applied for high‐precision isotope ratio measurement of these elements. Considering the total procedural blanks in LAF sampling, the minimum amounts required for high‐precision isotope measurement were 50, 2 and 20 ng for Sr, Nd and Pb, respectively. The LAF method has advantages over the conventional method. It also causes less damage in the test sample's depth direction and can be applied to samples with complex shapes. It is expected therefore that the LAF sampling method will be applied to geology and other research fields that require microsampling. Abstract : Key Points A new microsampling method, LAF, was evaluated for precise isotopic measurements of small‐sized geological materials. Isotope ratios of a glass reference material collected using LAF were measured by TIMS, and no isotopic fractionation was observed. LAF is applicable to samples with complex shapes.